Acquiring Scientific Process and Innovative Thinking Skills for Secondary School Sixth Grade Students through Digital Activities: An Action Research - Emine Akkaş Baysal; Ali Osman Yörük; İjlal Ocak (Universitas Pendidikan Indonesia, 2022)
This research aims to develop students' scientific process and innovative thinking skills using digital activities in distance and face-to-face education. A total of 12 sixth-grade students in a primary school participated in the study. The research was action research. The analysis was carried out in the